UPAYA MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR PENDIDIKAN AGAMA KRISTEN MELALUI PENERAPAN MODEL PEMBELAJARAN BUZZ GROUP DISCUSSION SISWA SMP NEGERI 2 GAROGA - LOMIDE PASARIBU (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
The implementation of this classroom action research aims to determine the increase in creativity and learning achievement of Christian Religious Education after the implementation of the Buzz Group Discussion learning model for Class VIII students of SMP Negeri 2 Garoga in the 2018/2019 academic year. The type of research used is classroom action research (CAR) applied to Class VIII students of SMP Negeri 2 Garoga in the 2018/2019 academic year with a total of 18 students consisting of 10 male students and 8 female students. Data collection techniques with test techniques, observation and documentation. The data analysis technique was processed by descriptive analysis. The results showed that learning Christian Religious Education with the Buzz Group Discussion model in class VIII students of SMP Negeri 2 Garoga in the 2018/2019 academic year was able to improve student learning achievement. The increase in learning outcomes in the pre-cycle with an average of 58.00, increased in the first cycle to 64.80 and in the last cycle to 74.80, while the number of students who completed was 3 students or 12.00% of the 25 students in the initial condition. , became 14 students or 56.00% and 24 students or 96.00% in the last cycle. The explanation of the increase in student learning creativity from 6 students or 24.00% in the initial conditions increased to 16 students or 64.00% and in the last cycle to 25 students or 100%. This shows that the learning achievement of students in the subject of Christian Religious Education in Class VIII of SMP Negeri 2 Garoga in the 2018/2019 academic year can be improved through the Buzz Group Discussion learning model because it has exceeded the classical completeness score, which is 95.00% above the KKM ( 70). From the results above, it can be concluded that through the Buzz Group Discussion learning model it is proven to be able to improve the learning process, learning creativity and learning achievement of Class VIII students of SMP Negeri 2 Garoga Semester 1 of the 2018/2019 Academic Year. ABSTRAKPelaksanaan penelitian tindakan kelas ini bertujuan untuk mengetahui peningkatan kreativitas dan prestasi belajar Pendidikan Agama Kristen setelah diterapkannya model pembelajaran Buzz Group Discussion pada peserta didik Kelas VIII SMP Negeri 2 Garoga Tahun Pelajaran 2018/2019. Jenis penelitian yang digunakan adalah penelitian tindakan kelas (PTK) diterapkan pada peserta didik Kelas VIII SMP Negeri 2 Garoga Tahun Pelajaran 2018/2019 dengan jumlah peserta didik 18 yang terdiri dari 10 peserta didik laki-laki dan 8 peserta didik perempuan. Teknik pengumpulan data dengan teknik tes, observasi dan dokumentasi. Teknik analisa data diolah dengan analisis deskriptif. Hasil penelitian menunjukkan, bahwa pembelajaran Pendidikan Agama Kristen dengan model Buzz Group Discussion pada peserta didik kelas Kelas VIII SMP Negeri 2 Garoga Tahun Pelajaran 2018/2019 mampu meningkatkan prestasi belajar peserta didik. Adapun peningkatan hasil belajar pada prasiklus dengan rata-rata 58,00, meningkat pada siklus I menjadi 64,80 dan pada siklus terakhir menjadi 74,80, sedangkan jumlah siswa yang tuntas sebanyak 3 siswa atau 12,00% dari 25 siswa pada kondisi awal, menjadi 14 siswa atau 56,00% dan 24 siswa atau 96,00% pada siklus terakhir. Penjelasan mengenai peningkatan kreativitas belajar siswa dari 6 siswa atau 24,00% pada kondisi awal meningkat menjadi 16 siswa atau 64,00% dan pada siklus terakhir menjadi 25 siswa atau 100%. Hal ini menunjukkan bahwa, prestasi belajar peserta didik pada mata pelajaran Pendidikan Agama Kristendi Kelas VIII SMP Negeri 2 Garoga Tahun Pelajaran 2018/2019 dapat ditingkatkan melalui model pembelajaran Buzz Group Discussion karena telah melampaui nilai ketuntasan secara klasikal yaitu 95,00% di atas KKM (70). Dari hasil di atas maka dapat disimpulkan bahwa melalui model pembelajaran Buzz Group Discussion terbukti dapat meningkatkan proses pembelajaran, kreativitas belajar dan prestasi belajar siswa Kelas VIII SMP Negeri 2 Garoga Semester 1 Tahun Pelajaran 2018/2019.